Free Model of Sentence Classifier for Automatic Extraction of Topic Sentences - Khodra, M.L.; Widyantoro, D.H.; Aziz, E.A.; Trilaksono, B.R. (Journal of ICT Research and Applications, 2013)
This research employs free model that uses only sentential features without paragraph context to extract topic sentences of a paragraph. For finding optimal combination of features, corpus-based classification is used for constructing a sentence classifier as the model. The sentence classifier is trained by using Support Vector Machine (SVM). The experiment shows that position and meta-discourse features are more important than syntactic features to extract topic sentence, and the best performer (80.68%) is SVM classifier with all features.